Efficacy and Safety Exposure‐Response Analyses of Olaparib Capsule and Tablet Formulations in Oncology Patients. Issue 6 (22nd February 2019) - Zhou, Diansong; Li, Jianguo; Learoyd, Maria; Bui, Khanh; Berges, Alienor; Milenkova, Tsveta; Al‐Huniti, Nidal; Tomkinson, Helen; Xu, Hongmei
Abstract : Olaparib is a poly ADP‐ribose polymerase inhibitor that induces synthetic lethality in tumors with deficient homologous recombination repair. Population exposure‐response analyses were performed to evaluate the efficacy and safety of olaparib exposure in patients with cancer. Data from multiple phase I/II/III clinical studies from both capsule and tablet formulations were combined for efficacy ( N = 410) and safety ( N = 757) analyses. Exposure‐progression‐free survival (Cox proportional hazards model indicated that a 300 mg b.i.d. tablet was statistically superior to the 200 mg b.i.d. tablet dose (hazard ratio of 0.96), although the difference was small. Exposure‐safety logistic regression models and hemoglobin models predicted similar probability of safety events or hemoglobin decrease with largely overlapping 95% confidence intervals at 300 mg b.i.d. tablet, 200 mg b.i.d. tablet, and 400 mg b.i.d. capsule. The analyses provided key assessments to support the approval of olaparib 300 mg tablet therapeutic dose in patients with ovarian and breast cancer, regardless of their breast cancer ( BRCA ) mutation status.